Strategi Pengembangan Pasar Daerah Berbasis Komoditas Unggulan - Sulis Rochayatun; Puji Handayati; Ratna Dwi Nastiti (Universitas Jember, 2018)
Regional markets, including traditional markets that are now turned into people's markets, are certain areas where buyers and sellers meet, both directly and indirectly, through the process of buying and selling various types of consumer goods through bargaining which is also a market developed and managed by the regency government or city in Indonesia. People's market focal points can be observed from their influence on the fulfillment of small people's livelihoods. That is why the people's market is a pillar of people's economy. The purpose of this study is to formulate a strategy for developing regional markets in Pasuruan Regency to improve the community's economy based on regional superior commodities. This research is a field research using a descriptive quantitative approach. This research was conducted in 14 regional markets in the Pasuruan Regency administrative region and 5 village markets The analysis shows that several factors are the strengths and weaknesses of traditional markets in Pasuruan Regency. The most prominent strength factor is that all of the markets sampled in this study are located in strategic locations. Whereas the most prominent weaknesses are lack of adequate sanitation (drainage is not functioning properly, bathroom, and toilet conditions, clean water is not all available, market disinfection has not been carried out, not yet free of vector / star of infectious diseases. Pasuruan Regency needs to revitalize traditional markets, namely physical renovations of market buildings, and accompanied by institutional building. Keywords: traditional market, superior product